1981
DOI: 10.1002/qj.49710745412
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic limitations to the release of latent heat during the natural and artificial glaciation of deep convective clouds

Abstract: S U M M A R YThe latent heat thermodynamically available in the supercooled water of deep convective clouds is released at rates governed by the glaciation mechanism, presumed here to involve primary nucleation, capture nucleation of rain by small ice particles and secondary ice production (rime-splintering hypothesis). A simple microphysical model of the glaciation shows the importance of regenerative feed-back on the evolution of ice when the primary nucleation and regenerative processes proceed simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Initiation of precipitation may also be triggered by cold processes [e.g., Lamb et al , 1981], but here we limit our study to the warm rain process where precipitation was initiated as raindrops, even when T* < 0°C, where rain initiates as supercooled water. We investigated here relationship between the N CCN at 0.4% SS (N 0.4% ) below the cloud base and N c above cloud base.…”
Section: Resultsmentioning
confidence: 99%
“…Initiation of precipitation may also be triggered by cold processes [e.g., Lamb et al , 1981], but here we limit our study to the warm rain process where precipitation was initiated as raindrops, even when T* < 0°C, where rain initiates as supercooled water. We investigated here relationship between the N CCN at 0.4% SS (N 0.4% ) below the cloud base and N c above cloud base.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that supercooled raindrops play an important role in the ice process (e.g. Koenig, ; Lamb et al , ; Phillips et al , ). The model results herein are consistent with those of Chisnell and Latham () and Blyth and Latham ().…”
Section: Discussionmentioning
confidence: 99%
“…Results of calculations performed by Chisnell and Latham () showed that supercooled raindrops can play an important role in the glaciation of clouds by the HM rime‐splinter mechanism because instant rimers are produced when the raindrops freeze. Later modelling studies by, for example, Koenig (), Lamb et al (), Phillips et al (), Sun et al () and Crawford et al () further illustrated the importance of supercooled raindrops in the HM multiplication process. In addition, Chisnell and Latham () found that the rate of glaciation may be substantially enhanced if the raindrops themselves produced splinters as they froze.…”
Section: Introductionmentioning
confidence: 98%
“…It is now understood that the amount of supercooled water in the TCs is too small to expect much of a seeding effect upon freezing, and this small amount of water freezes naturally quickly above the 0°C level. As shown in several modeling studies (Cotton 1972;Koenig and Murray 1976;Scott and Hobbs 1977), the presence of these large drops enhances the rapidity of glaciation of clouds and also produces greater concentrations of ice particles by the rime-splinter ice multiplication process (Hallett and Mossop 1974;Koenig 1977;Lamb et al 1981). Much of the rain precipitates without ever freezing (e.g., Khain et al 2008a;).…”
Section: Ackground and Motivationmentioning
confidence: 96%